The Many Faces of Poverty in Sub-Saharan Africa - World Bank (Washington, DC, 2012)
This report compares poverty levels and trends in sub - Saharan Africa with the rest of the world. It then uses national aggregate indicators to look at poverty trends and levels across African countries. This section makes use of demographic, economic and social indicators from the Bank's socioeconomic database and other international sources. The report then highlights the many faces of poverty in Africa by drawing from household survey data to look at the diversity of poverty at the sub-national level - specifically, how poverty is distributed within countries, and what are the common socioeconomic characteristics of the poor, including where they live, the composition of households, access to social services and employment opportunities, and consumption habits. Gender is a fundamental feature of any discussion on poverty and welfare and is therefore interwoven throughout the report.